Information search trends about sharia: a comparation study between business-industry genre with book-literature genre - Akhmad Kusuma Wardhana (Journal of halal product and research (JPHR), 2020)
Indonesia has a large sharia market potential. This is because Indonesia has the largest Muslim population in the world. The market potential is supported by the openness of information via the internet. This study aims to observe trends in information search on the internet about sharia with comparative studies on the genre of "business-industry" with the genre of "book-literature". The approach in this research is descriptive qualitative with the method of a literature study to collect data. The primary data of this study are the trends in sharia information sought by internet users throughout 2019. The results of the study indicate that the trend of information about sharia with the "business-industry" genre is more than the "book-literature" genre. The trend of seeking information about halal is the most trend in both genres, while the trend of finding the least information is information about sharia research.